Тенденції розвитку та впровадження цифрових технологій для реалізації цілей сталого розвитку - Федулова, Л.І. (Економіка природокористування і сталий розвиток, 2020)
Охарактеризовано світові тенденції розвитку та впровадження цифрових технологій для реалізації Цілей сталого розвитку (ЦСР) в умовах цифровізації економіки і суспільства, зокрема: комплексний вплив технологій індустрії 4.0 на досягнення цілей, цифрові технології як драйвер нового етапу сталого розвитку і відкриття нових ринків, посилення ролі міжнародних організацій в актуалізації політики цифрового розвитку. Проаналізовано стан цих процесів в Україні та розроблено пропозиції щодо забезпечення їх результативності. The paper identifies and characterizes global trends in the development and introduction of digital technologies for implementation of the Sustainable Development Goals (SDGs) in the context of digitalization of the economy and society, including the integrated impact of 4.0 industry technologies on the achievement of sustainable development goals, digital technologies as a driver of a new stage of sustainable development and new markets discovery, strengthening the role of international organizations in updating digital development policy. Practical examples of the Sustainable Development Goals implementation have been analysed and the provision has been substantiated that the breakthroughs in the field of digital technologies have already led to wealth creation in an unprecedentedly short time, concentrated, however, in a small number of countries, companies and individuals. The aforesaid indicates the existence of «digital inequality», which poses serious tasks for the decision-making bodies of states to develop mechanisms for its elimination or reduction. The status of these processes in Ukraine has been identified and the following has been revealed: a number of electronic administrative services for individuals and legal entities and the Unified State Portal of Administrative Services were introduced, a new generation of digital technologies is being introduced into the industry, such as Internet of Things, cloud computing, big data and data analytics, robotics, and 3D printing that open new horizons for innovative products and services development. It has been established that our state is not yet sufficiently transforming the capabilities of modern digital technologies into economic and social benefits (digital dividends): there is no systematic approach to the implementation of the approved measures, no digital competencies are being formed, including for the population, there is a detachment from the SDGs Strategy. The proposals on actualization of these issues and their heading in the direction of processes and formation socialization of the newest model of the international relations environment, in particular in the elaboration of geopolitical values, implementation of the principles of «sustainable development» in the digital transformation of economy and society on the basis of integration and controllability.